Ozone I: Characteristics/Generation/Possible Applications - Heim, Carolin; Glas, Karl (BrewingScience, 2011)
Due to its high oxidative potential, ozone is a highly reactive molecule that is able to oxidize and mineralize inorganic and organic materials. In water, ozone decomposes into oxygen for which reason it seems to be an ideal candidate for removal of persistent substances and microbes during water treatment. Today, ozone is widely applied in water processing of drinking and process water. Other possible applications for treatment and disinfection of surfaces in medical areas and food processing are currently under development and will be further described in the next part of this article series. This review gives an overview over the current state-of-the art in ozone production and possible operational areas.